2003
DOI: 10.1053/jhep.2003.50016
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of hepatitis A vaccination in children, adolescents, and adults

Abstract: Hepatitis A is a major public health problem in the United States and other developed countries, largely because decreased natural immunity allows for increased susceptibility. To evaluate the cost-effectiveness of routine vaccination of children, adolescents, and certain high-risk adults against hepatitis A, economic analyses of hepatitis A vaccination were identified through searches of MEDLINE, EMBASE, and BIOSIS (February, 1992, to December, 2001) for studies, reviews, editorials, and letters from peer-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 60 publications
0
31
0
9
Order By: Relevance
“…One the one hand, in the highly endemic regions, it is almost impracticable to identify the groups at risk for acquiring the disease; and on the other, the high cost of vaccine makes it difficult to extend this benefit to the entire population. [45][46][47] Israel was the first country to adopt universal vaccination for children at 18 and 24 months of age in June 1999, and the results were excellent. 48 A very recent analysis of the impact of this program, 5.5 years after it began, reveals that an important decline has been observed in the incidence of the disease in all age groups, with 90%…”
Section: Impact Of Anti-hav Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…One the one hand, in the highly endemic regions, it is almost impracticable to identify the groups at risk for acquiring the disease; and on the other, the high cost of vaccine makes it difficult to extend this benefit to the entire population. [45][46][47] Israel was the first country to adopt universal vaccination for children at 18 and 24 months of age in June 1999, and the results were excellent. 48 A very recent analysis of the impact of this program, 5.5 years after it began, reveals that an important decline has been observed in the incidence of the disease in all age groups, with 90%…”
Section: Impact Of Anti-hav Vaccinationmentioning
confidence: 99%
“…49 Children at pre-school age must be the main focus of immunization strategies, because of their critical role in virus transmission. 21, [45][46][47]50 As has been demonstrated by different studies, the efficient way to diminish incidence of the disease and even eradicate the infection is mass vaccination of children. There are, however, many barriers to this measure being adopted, among them: the growing number of vaccinations in childhood, other public health priorities, the cost of vaccine and the reduced number of cost-effectiveness studies of this strategy for our country.…”
Section: Impact Of Anti-hav Vaccinationmentioning
confidence: 99%
“…Nowadays Hepatitis A vaccine is recommended in USA and Israel [25,26]. Rosenthal P. [27] reviewed some economical analysis about Hepatitis A vaccine and he concluded that its economical benefit is similar the other vaccines that are included in the routine child immunization program. Besides this, it is economically acceptable for adolescents and adults who have a high risk to get this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nas localidades do semi-árido do Nordeste, especialmente os de menor porte, como Cavunge, a poluição ambiental é talvez o maior determinante de várias doenças de transmissão fecal-oral e decorrente de múltiplos fatores, tanto sanitários como culturais 4 .…”
Section: Discussionunclassified